2017
DOI: 10.1016/j.pharep.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical testing of drug activities at the cellular level: Case study for endothelium-targeted drugs

Abstract: The anti-inflammatory activity of the simvastatin is well illustrated by the endothelium cell elasticity changes returning from the characteristic inflammation time cycle "soft-stiff-soft" to control values. Furthermore, the elasticity results and F-actin labeling data indicated a preventive effect for 1- MP, whereas 1,4-DMP does not exhibit endothelium activity even at toxic concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It was observed that the SMV and CnO amounts had a significantly negative effect on IL-6 levels, whereas the Smix ratio had a significantly positive effect on the same parameter (p < 0.0001). The decrease in IL-6 levels observed with an increase in the SMV amount could be referred to as an SMV antiinflammatory characteristic [38]. It is well established that statins can lower the production of proinflammatory cytokines [39] by inhibiting HMG-CoA reductase, which would activate the mevalonate pathway.…”
Section: Interleukin-6 Measurementsmentioning
confidence: 99%
“…It was observed that the SMV and CnO amounts had a significantly negative effect on IL-6 levels, whereas the Smix ratio had a significantly positive effect on the same parameter (p < 0.0001). The decrease in IL-6 levels observed with an increase in the SMV amount could be referred to as an SMV antiinflammatory characteristic [38]. It is well established that statins can lower the production of proinflammatory cytokines [39] by inhibiting HMG-CoA reductase, which would activate the mevalonate pathway.…”
Section: Interleukin-6 Measurementsmentioning
confidence: 99%
“…AFS was used in the broadly understood nano‐diagnosis in cancer cell, which shows higher elasticity of tumor cells compared with normal cells. Additionally, force spectroscopy can be useful to detect changes in the mechanical phenotype of various cell lines affected by hormones, high glucose level, cytokines, or drugs . Using force spectroscopy, one can obtain maps of the elasticity modulus within a single cell or tissue .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, statins exert anti-inflammatory properties [ 7 ] and inhibit that of the proinflammatory cytokines [ 8 ]. The anti-inflammatory effect of statins has been attributed to their ability to reduce, by inhibiting HMG-CoA reductase, not only cholesterol synthesis but also the activation of the mevalonate pathway, with the consequent reduction of isoprenylated and geranylgeranylated proteins, and in particular of Ras prenylation.…”
Section: Introductionmentioning
confidence: 99%